Audit Sistem Enterprise Resources Planning â€œOracle Fusion Applicationâ€ menggunakan Framework COBIT 5 (Studi Kasus di FITB Institut Teknologi Bandung) - Sinaga, Frendy; Nugraha, Darya Setia (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The establishment of Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions is the foundation for every company, state administrator, business entities, and the public to organizing, managing, and operating their activities. As well as the Bandung Institute of Technology, is supported and adopts the ERP System